Mengenali dan Melawan Hoax di Media Sosial Facebook - Moh. Wahyuddin S. Adam; Ade Seftiyani Botutihe; Maysaraswati Biko; Nurain Mohammad (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
A hoax or fake news on social media refers to information that is spread with the intent to mislead or confuse people, often without valid factual basis. This phenomenon has become increasingly prevalent, especially on platforms like Facebook, where information can spread quickly. Therefore, the way to recognize and combat hoaxes on social media, particularly Facebook, is by carefully checking the source of information, verifying facts through trustworthy websites, and being cautious of sensational headlines and images that seem relevant. Additionally, checking the date and time of the information is crucial to avoid falling for outdated or manipulated content. In this context, verification plays a vital role in helping users be more discerning when filtering news and preventing the spread of hoaxes. If we fail to recognize or combat hoax dissemination, the impact can be highly detrimental to individuals and society, leading to confusion, panic, and both material and psychological harm. Therefore, raising awareness and media literacy among the public is essential to reduce the negative impact of hoaxes, encouraging people to be more critical and responsible in sharing information.